Small Target Detection Within Sea Clutter Based on Fractal Analysis. (2016) - Jayaprakash, Arunprakash; Reddy, G. Ramachandra; Prasad, N.S.S.R.K.
Abstract: Sea clutter refers to the signals returned from the wavy and turbulent rough sea surface. The radar returns from small targets, like submarine periscope or small boats, will be obscured by the sea clutter which makes the straightforward detection of targets, with small radar cross section, a difficult task. The conventional target detection schemes in the presence of sea clutter are mainly based on Hurst exponent, estimated utilizing the fractal characteristics of the received radar data. In the present study, a more robust signature measure is proposed based on fractal analysis of received radar data. The proposed target detection method is applied on actual sea clutter radar data and the performance is compared with the conventional Hurst parameter based method. The simulation results illustrate that the proposed method achieves better detection performance and is robust under varying sea conditions.